Ordained Ministry in Free Church Perspective : Retrieving Robert Browne (c. 1550-1633) for Contemporary Ecclesiology - Abrahamse, Jan Martijn, (Religious Studies, Theology and Philosophy E-Books Online, Collection 2020, ISBN: 9789004419094., 2021)
In Ordained Ministry in Free Church Perspective Jan Martijn Abrahamse presents a constructive theology of ordained ministry by returning to the life and thought of the English Separatist Robert Browne (c. 1550-1633). This study makes a substantial contribution not only by solving one of the most thorny problems in congregational ecclesiology, but also by recovering the legacy of this ecclesial pioneer. Through an in-depth analysis of Browne's literature, the author provides a covenantal theology of ordained ministry in conversation with present-day authors Stanley Hauerwas and Kevin Vanhoozer. Inspired by the emerging trend of 'theology of retrieval' Abrahamse offers a methodologically innovative way of doing systematic theology in a manner in which voices from the past can be made fruitful for today.